2022
DOI: 10.1007/s11095-022-03215-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Viable Skin Concentration: Modelling the Subpapillary Plexus

Abstract: The skin concentration of a substance after a topical application or exposure determines both local treatment outcomes and the dermal toxicity assessment of various products. However, quantifying the time course of those concentrations at skin effect sites, such as the viable epidermal, superficial dermis and appendages in humans is especially problematic in vivo, making physiologically based mathematical modelling an essential tool to meet this need. This work further develops our published physiologically ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Attention was paid to the function and reperfusion of dermal capillary loops during the angiogenic immune response. [15][16][17] The thermal trends observed in the murine model, supported by the results of the computer simulations, suggest that ETI may be able to capture intricacies of the healing process that are overlooked by other imaging methods.…”
Section: Introductionmentioning
confidence: 67%
“…Attention was paid to the function and reperfusion of dermal capillary loops during the angiogenic immune response. [15][16][17] The thermal trends observed in the murine model, supported by the results of the computer simulations, suggest that ETI may be able to capture intricacies of the healing process that are overlooked by other imaging methods.…”
Section: Introductionmentioning
confidence: 67%
“…The BITES platform presented in this study possessed microvessel structures (in contrast to Reuter et al) and these were approximately an order of magnitude smaller in diameter than those described in the Janson et al report [ 20 ]. The smaller diameters more closely approximate the sizes of microvessels found at depths in the dermis that mosquitoes access for blood-feeding [ 48 , 59 , 67 ]. Further—distinct from Janson et al—these BITES microvessel structures resulted from Capgel self-assembly, thus not requiring 3D printing, and were cellularized.…”
Section: Discussionmentioning
confidence: 98%
“…As with the blood-loaded Capgel, HDF cellularization did not prevent the free movement/flow of blood within the BITES microvessels ( Figure 7 B,C, Videos S7 and S8 ). A DIC micrograph and corresponding 3D-rendered depth profiling of the situation revealed that the mosquito pushed the fascicles of stylet mouthparts ~500 µm into the BITES tissue, a depth at which dermal microvessels would be encountered in humans ( Figure S3 ) [ 48 , 59 ]. A closer inspection of this penetration by DIC microscopy in the capview and raftview orientations showed that several layers of the microvessel structures were pierced ( Figure 7 D–I, respectively) and a track with an irregular “interaction volume” was created ( Figure 7 G–I, green dashed lines).…”
Section: Discussionmentioning
confidence: 99%
“…Because multiple solid microneedles are usually arranged in an array at the same distance, a representative elementary volume (REV) is chosen for numerical simulations, as shown in Figure 2 . The 2D axis-symmetric configuration comprises a patch that loads nanocarriers, a cavity left after the withdrawal of the microneedle, and the skin layers; their real thicknesses [10] are specified in Figure 2 . The morphological features of solid microneedles can vary significantly depending on a particular design.…”
Section: Methodsmentioning
confidence: 99%